RELAÇÕES ENTRE ÁREAS VERDES E A VITALIDADE URBANA NO PLANEJAMENTO DAS CIDADES - Covaleski, Joani Paulus; Pessotto, Wellerson; Alves, Alessandro; Romano, Fabiane Vieira (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Considering that the city is not only a form of settlement, or a space of distribution of goods and services, but the product of an accumulation of characteristics of a local and susceptible actions made by several actors, it is up to the urban planning, to realize the most diverse forecasts and seek to meet needs in the short and long term, seeking to promote quality of life and ambience in space. In order to minimize the impacts of urban centers, three important urban planning models and spatial ordering principles were correlated in order to visualize factors that contribute to the qualification of city life. With a focus on urban planning and the incumbency of green spaces and building spaces in the whole and their influence on the vitality of the city, it is possible to highlight the importance of the presence of these spaces in the urban network, historically speaking and exponentially highlighting the advance technological.